VISUAL AIDS FOR TEACHING ENGLISH TO STUDENTS WITH AUTISM SPECTRUM DISORDER - Ni Putu Intan Bidari; Made Vera Yanti (English Department, STKIP PGRI Bandar Lampung, 2021)
English is a language that is used by people around the world. Hence, it is necessary for everyone to learn it, including the students with special needs. This study aims to review the use of visual aids in teaching English for students with special needs, especially Autism Spectrum Disorder. The study is a library study that focuses on collecting theoretical and empirical studies about the use of visual aids in teaching students with ASD. Autism Spectrum Disorder is a neurological disorder that affects the function of the human brain. Visual aids are the tools or devices that are shown by the teacher in the classroom to help students understanding the learning materials. The study finds that the use of visual aids is effective for teaching English to students with Autism Spectrum Disorder. Therefore, teachers should consider using visual aids in teaching autistic students. This study is expected to give insightful information in educational fields.